Pharmacological and Non-Pharmacological Interventions for Improving Quality of Life in Dementia Care: Review Article (Journal of Pharma Insights and Research, 2025)
Dementia is characterized by progressive cognitive decline, behavioral changes, and diminished independence. Current pharmacological interventions, including cholinesterase inhibitors, memantine, and antipsychotics, demonstrate variable efficacy in improving quality of life (QoL) and are often limited by adverse effects. Non-pharmacological interventions (NPIs) are being used as crucial components in dementia management, particularly in residential and community settings. Cognitive stimulation therapy has shown robust evidence for QoL improvement, while physical exercise, reminiscence therapy, music therapy, and cognitive rehabilitation show promising outcomes. Analysis of systematic studies reveals the significance of person-centered care models that combine psychosocial, emotional, and spiritual aspects alongside conventional medical management. Complementary approaches, including occupational therapy, art therapy, and sensory-based interventions, contribute variably to patient well-being. Implementation barriers and methodological limitations in current research necessitate stronger evidence for emerging therapies and development of practical guidelines for translating NPIs into clinical practice. Recent advances in digital biomarkers, artificial intelligence tools, and hybrid care models offer new opportunities for personalizing interventions and monitoring disease progression. The use of pharmacological and non-pharmacological interventions, coupled with early detection strategies and risk management, shows a promising direction for optimizing QoL in dementia care.